2017
DOI: 10.1136/sextrans-2016-053069
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of studies evaluating the performance and operational characteristics of dual point-of-care tests for HIV and syphilis

Abstract: AbstrActbackground Mother-to-child transmission (MTCT) of syphilis and HIV continue to be important yet preventable causes of perinatal and infant morbidity and mortality. Objectives To systematically review, critically appraise and perform a meta-analysis to evaluate the operational characteristics of dual rapid diagnostic tests (RDTs) for HIV/syphilis and evaluate whether they are cost effective, acceptable and easy to use. Design Systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 51 publications
(70 reference statements)
5
71
0
1
Order By: Relevance
“…The dual RDT was more cost effective than single RDTs and prevented more adverse outcomes of pregnancy. Qualitative data indicated that dual tests were acceptable in terms of turnaround time, cost and a single finger prick .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual RDT was more cost effective than single RDTs and prevented more adverse outcomes of pregnancy. Qualitative data indicated that dual tests were acceptable in terms of turnaround time, cost and a single finger prick .…”
Section: Resultsmentioning
confidence: 99%
“…A review by Gliddon et al. showed that the diagnostic accuracy of the HIV component of the dual test ranged from 94% to 99% sensitivity and from 92% to 100% specificity. The syphilis diagnostic accuracy ranged from 47% to 96% sensitivity and 90% to 100% specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Countries need to harness the architecture provided by HIV PMTCT programmes to screen women for both infections using a single drop of blood in a single visit to a health care facility. Dual rapid HIV-syphilis RDTs with acceptable performance are now available 36 and the WHO, as well as many countries, has adopted these HIV and/or syphilis RDTs into their national guidelines 31,37 .…”
Section: Malariamentioning
confidence: 99%
“…Additionally, dual syphilis/HIV rapid tests are available to screen for HIV and treponemal antibodies using a single lateral flow immunochromatographic strip. These are an increasingly important tool in the global elimination of MTCT of HIV and syphilis in settings in which laboratory capacity is limited 159 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%